Glass powder for MLCC and preparation method thereof, conductive copper paste and sintering process

By doping MnO2, CaO and ZrO2 in the BaO-ZnO-B2O3 system glass powder, and combining copper powder and organic carrier to form a conductive copper slurry, the copper end electrode was prepared by an integrated sintering process, which solved the problems of poor wetting and low sintering density at high temperatures, and improved the reliability of MLCC and product qualification rate.

CN118359383BActive Publication Date: 2025-03-11EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202410580049.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2025-03-11
Estimated Expiration
2044-05-11

AI Technical Summary

Technical Problem

The existing glass powder used in NP0 ceramic MLCC has poor wetting properties, low sintering density and poor electroplating fluid performance at high temperatures, resulting in insufficient density during sintering, easy oxidation, nickel seepage during electroplating, and low end binding force, which reduces the reliability and product pass rate of MLCC.

Method used

The glass powder of BaO-ZnO-B2O3 system was used, and MnO2, CaO and ZrO2 were doped on it. The glass powder was prepared by quenching by a double-roller rolling mill and ball milling and sieving. The conductive copper slurry was formed by combining copper powder and organic carrier, and the copper end electrode was prepared by an integrated sintering process.

Benefits of technology

It improves the high-temperature wetting and sintering density of glass powder, enhances the binding force with NP0 porcelain media, improves the chemical stability of the plating solution, avoids cracks and cracks during the electroplating process, and improves the reliability of MLCC and product qualification rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HHA0000009665970000011
    Figure HHA0000009665970000011
  • Figure HHA0000009665970000012
    Figure HHA0000009665970000012
  • Figure HHA0000009665970000013
    Figure HHA0000009665970000013
Patent Text Reader

Abstract

The present invention discloses a glass powder for NP0 ceramic MLCC and a preparation method thereof, a conductive copper paste and a sintering process. The glass powder raw materials for NP0 ceramic MLCC include: a basic glass component and an externally doped component; wherein the basic glass component is BaO-ZnO-B2O3 system glass, and the externally doped component is MnO2, CaO and ZrO2. The glass powder has a low glass softening temperature T f , a wider ΔT and a higher flow temperature FT, and at the same time, it has a relatively low wetting angle with NP0 ceramics, good wettability and adhesion. The conductive copper paste prepared by the glass powder, copper powder and organic carrier, combined with the copper terminal electrode prepared by the three-stage sintering process of the present invention, has excellent density and no nickel penetration. The internal stress of the MLCC product is small and moderate, the terminal tensile force is large, and the reliability test pass rate such as solder resistance and non-destructiveness is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chip passive components, and in particular to a glass powder, a conductive copper paste, a multilayer ceramic capacitor and a preparation method of an NP0 ceramic dielectric MLCC. Background Art

[0002] The vision of "carbon peak and carbon neutrality" points the way for the development of new energy vehicles, photovoltaics and other industries, and also provides an opportunity for the development of the upstream power electronics passive components industry. Domestic independent brand car companies such as BYD and Xiaopeng are seizing the opportunity of new energy transformation and rapidly promoting the electrification and intelligent upgrading of automobiles. As the world's most widely used passive component, MLCC has a wide range of applications in automotive electronics, consumer electronics, communication base stations, photovoltaics and other fields. In order to meet the requirements of the rapidly developing new energy vehicles and 5G communications for large capacity, high speed and integration of MLCC, MLCC will develop in the direction of higher frequency of use, miniaturization, large capacity, high reliability and low cost.

[0003] The sintered electrode copper paste is composed of metal copper powder, inorganic glass powder, organic carrier, additives, etc. The glass powder assists the sintering of the functional phase copper powder in the formation of the terminal electrode and provides adhesion for the connection of the internal and external electrodes. NP0 ceramic MLCC has higher requirements for the sintering temperature, sintering density, and terminal bonding of the terminal electrode, which in turn increases the requirements for the sintering-assisting characteristics, adhesion, and acid resistance of the glass powder. At present, the glass powder used to prepare the MLCC terminal electrode slurry has the disadvantages of poor high-temperature wettability, high sintering temperature, low density, and poor corrosion resistance of the electroplating solution. As a result, the copper powder of the MLCC terminal electrode is not dense, easy to oxidize, nickel infiltration during the electroplating process, and low terminal bonding. The above problems greatly reduce the reliability of MLCC, reduce the product qualification rate of MLCC, and thus greatly limit the application of MLCC in the high-end market. Therefore, it is necessary to develop a glass powder with high wettability, high bonding, and low temperature sintering for the preparation of high-reliability NP0 ceramic MLCC.

[0004] Low melting point glass includes lead, bismuth, tellurium and boron zinc silicon glass systems. The patent with application publication number CN115836032A discloses a lead-containing glass powder that can improve the silver dissolving and silver precipitation ability of glass materials under low temperature conditions, solving the problem that TOPCON crystalline silicon batteries cannot be metallized at low temperature. However, with the development of the times and people's demand for green environmental protection, the global research and development and production of new lead-free products has become a development trend. The glass powder disclosed in the patent with authorization announcement number CN114835404B does not contain lead toxic elements, and the sintering temperature is 650~750℃. After the glass powder is sintered, it has good wettability and strong adhesion with the MLCC ceramic matrix. There is no cracking and etching after being corroded by the electroplating solution. The chemical properties are stable, but the cost of the glass powder is relatively high, and the density of the copper terminal electrode morphology needs to be optimized. Patents with application publication numbers CN115925265A and CN114409251A respectively disclose Bi-containing low-temperature sintered glass systems and apply them in photovoltaics, packaging and other fields. However, during the slurry sintering process, Bi easily reacts chemically with BaTiO3 in the MLCC ceramic matrix, increasing the stress between the ceramic matrix and the metal terminal electrode and reducing product reliability. Patents with application publication numbers CN113724912A use composite copper powder and Bi-based and Zn-based glass compounding, sintering at 680-700°C to form a dense copper slurry, but the composition is relatively complex, there are too many preparation processes, and the reaction of Bi elements with the ceramic substrate needs to be optimized. Closer to this technical field is the patent application with publication number CN116535097A, which discloses boron zinc silicon crystallized glass powder for MLCC. It has strong adhesion to BaTiO3, high acid resistance and density, but the crystallized glass powder is easy to cause porcelain cracking in NP0 porcelain medium, and dielectric polarization cracking is easy to occur in non-destructive testing experiments, thereby reducing the reliability of the product. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, and to propose a glass powder, a conductive copper paste and a preparation method for NP0 ceramic MLCC, so as to solve the technical problems in the prior art of low high-temperature wettability, weak terminal bonding force, large internal stress of the ceramic, poor resistance to electroplating solution and low sintering density of the glass powder used for NP0 ceramic MLCC copper end paste.

[0006] First, the present invention provides a glass powder for NP0 ceramic MLCC, the raw materials of which include: a basic glass component and an externally doped glass component; wherein the basic glass component is BaO-ZnO-B2O3 system glass, the externally doped glass component is MnO2, CaO and ZrO2, and the mass ratio of the basic glass component to MnO2, CaO and ZrO2 is 100: (3.5~6.5): (1~5.5): (0~1).

[0007] Secondly, the present invention provides a method for preparing glass powder for MLCC with NP0 ceramic dielectric, comprising the following steps:

[0008] Weighing the raw materials of the basic glass components, grinding and mixing them into raw material solid powder and sintering them into glass liquid;

[0009] The glass liquid is poured into a double-roll sheet mill for quenching, and crushed into glass particles after cooling;

[0010] The raw materials of the externally doped glass component are weighed, ground and mixed into raw material solid powder;

[0011] Sintering the externally added raw material solid powder and the glass particles of the basic component into glass liquid;

[0012] The glass liquid is poured into a double-roll sheet mill for quenching, and crushed into glass particles after cooling;

[0013] The glass particles are ball-milled and sieved in sequence to obtain glass powder.

[0014] Then, the present invention provides a conductive copper paste for MLCC with NPO ceramic dielectric, the raw materials of which include: copper powder, organic carrier and glass powder for MLCC provided by the first aspect of the present invention.

[0015] Finally, the present invention provides a sintering process for conductive copper paste for NP0 ceramic dielectric. The conductive copper paste of the present invention is applied to NP0 ceramic dielectric MLCC. The sintering process includes a debinding zone, a sintering insulation zone, and a cooling zone.

[0016] Compared with the prior art, the beneficial effects of the present invention include:

[0017] The BaO-ZnO-B2O3 glass powder prepared by the present invention contains MnO2, CaO and ZrO2. 2+ / Ca 2+ In the glass structure, the barium zinc boron system glass powder with the addition of MnO2 / CaO can effectively reduce its sintering temperature and improve the wettability with NP0 ceramic medium, enhance the bonding force between glass powder and NP0 ceramic medium, and at the same time, the addition of ZrO2 can enhance the chemical stability of glass powder in the electroplating solution, which can effectively avoid the cracks and cracks caused by the acidic electroplating solution during the electroplating process of MLCC terminal electrodes. The glass powder has a lower glass softening temperature T f, wider ΔT, higher flow temperature FT, etc., and at the same time, it has good wettability with NP0 ceramic dielectric and a low wetting angle. The conductive copper paste formed by mixing the glass powder with copper powder and an organic carrier, combined with the copper terminal electrode prepared by the integrated sintering process of the present invention, has the advantages of low porosity, high sintering densification, and high electroplating qualification rate. After sintering, the MLCC device has a small and moderate internal stress, large end tension, and a high qualification rate for reliability tests such as solder resistance and non-destructiveness. The glass powder, conductive copper paste and sintering process of the present invention also have the advantages of simple preparation process, high efficiency, and high product qualification rate; BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 is the sintering wetting angle of the glass powder prepared in Comparative Example 1 and Examples 1 to 3 of the present invention; wherein, Comparative Example 1 is 88°, Example 1 is 73°, Example 2 is 63°; and Example 3 is 50°;

[0019] Figure 2 This is the SEM microscope spectrum of the electroplating solution after corrosion prepared in Comparative Example 2 and Examples 1 to 3 of the present invention;

[0020] Figure 3 It is a SEM characterization picture of the terminal electrode morphology of comparative example 1 and embodiments 1 to 3 of the present invention;

[0021] Figure 4 The copper electrode tip tensile test results of Comparative Example 1 and Examples 1 to 3 of the present invention are shown in FIG. 1 , 1 and 2. Each example has 8 samples. Figure 4 The horizontal axis represents the sample number.

[0022] Embodiment 1:

[0023] This case provides a method for preparing glass powder and conductive copper paste, and a conductive copper paste sintering process.

[0024] (1) The basic glass component raw materials BaO, ZnO, B2O3 and SiO2 powders were weighed in a mass percentage of 40:30:17:13, ground and mixed into a uniform solid powder, placed in a crucible, and heated to 1300°C at a heating rate of 10°C / min and kept warm for 120 min to ensure that the glass raw materials were completely melted into glass liquid. The glass liquid was poured into a double-roll sheet mill for quenching and crushed after cooling.

[0025] (2) The mass ratio of the externally doped oxides MnO2, CaO and ZrO2 is 2:3:1. The externally doped glass components are ground and mixed into a uniform solid powder, which is placed in a crucible together with the base glass fragments. The temperature is raised to 1100°C at a heating rate of 15°C / min and kept warm for 30 min to ensure that the glass raw materials are completely melted into glass liquid. The glass liquid is poured into a double-roll sheet mill for quenching and crushed after cooling.

[0026] (3) Pour all the glass particles into a ball mill and grind them evenly using a ball mill at a speed of 200 r / min. Grind for 60 minutes and then pass through a 200-mesh sieve.

[0027] (4) Add deionized water to the coarse powder at a mass ratio of 1:2, and grind it again using a ball mill at a speed of 150 r / min. After grinding for 90 minutes, pass it through an 800-mesh sieve.

[0028] (5) Pour the ground water-glass suspension into a tray and place it in an oven for drying. After the water is completely evaporated, sieve it with a 100-mesh sieve to obtain glass powder.

[0029] (6) Glass powder, copper powder and organic carrier are mixed uniformly in a mass ratio of 10:65:25 to prepare a slurry.

[0030] (7) The slurry is coated on both ends of the ceramic body and sintered to prepare copper-terminal electrodes. The debinding temperature is 550-600°C and the temperature is kept for 30 minutes. The sintering temperature is 750°C and the temperature is kept for 12 minutes. The cooling zone is cooled from 500°C to 100°C at a cooling rate of 20°C / min.

[0031] like Figures 1 to 4 As shown, the glass powder has good high-temperature wettability, with a wetting angle of 73°. After acid etching, the glass phase has no obvious cracks and a smooth morphology. After sintering, the electrode surface has good density, no holes, puncture pinholes, or bulging. The inner copper terminal electrode adheres closely to the ceramic body, the stress is moderate and evenly distributed, and the terminal tension is greater than 6LB.

[0032] Embodiment 2:

[0033] This case provides a method for preparing glass powder and conductive copper paste, and a conductive copper paste sintering process.

[0034] (1) The basic glass component raw materials BaO, ZnO, B2O3 and SiO2 powders were weighed in a mass percentage of 30:40:20:10, ground and mixed into a uniform solid powder, placed in a crucible, and heated to 1200°C at a heating rate of 10°C / min and kept warm for 90 min to ensure that the glass raw materials were completely melted into glass liquid. The glass liquid was poured into a double-roll sheet mill for quenching and crushed after cooling.

[0035] (2) The mass ratio of the externally doped oxides MnO2, CaO and ZrO2 is 4:3:0.5. The externally doped glass components are ground and mixed into a uniform solid powder, which is placed in a crucible together with the base glass fragments. The temperature is raised to 1000°C at a heating rate of 15°C / min and kept at this temperature for 30 min to ensure that the glass raw materials are completely melted into glass liquid. The glass liquid is poured into a double-roll sheet mill for quenching and crushed after cooling.

[0036] (3) Pour all the glass particles into a ball mill and grind them evenly using a ball mill at a speed of 200 r / min. Grind for 45 minutes and then pass through a 200-mesh sieve.

[0037] (4) Add deionized water to the coarse powder at a mass ratio of 1:2, and grind it again using a ball mill at a speed of 150 r / min. After grinding for 120 minutes, pass it through an 800-mesh sieve.

[0038] (5) Pour the ground water-glass suspension into a tray and place it in an oven for drying. After the water is completely evaporated, sieve it with a 100-mesh sieve to obtain glass powder.

[0039] (6) Glass powder, copper powder and organic carrier are mixed uniformly in a mass ratio of 10:65:25 to prepare a slurry.

[0040] (7) The slurry is coated on both ends of the ceramic body and prepared into copper-terminal electrodes after sintering. The debinding temperature is 550-600°C and the temperature is kept for 30 minutes. The sintering temperature is 720°C and the temperature is kept for 12 minutes. The cooling zone is cooled from 500°C to 100°C at a cooling rate of 20°C / min.

[0041] like Figures 1 to 4 As shown, the glass powder has good high-temperature wettability, with a wetting angle of 63°. After acid etching, the glass phase has no obvious cracks and a smooth morphology. After sintering, the electrode surface has good density, no holes, puncture pinholes, or bulging. The inner copper terminal electrode adheres closely to the ceramic body, the stress is moderate and evenly distributed, and the terminal tension is greater than 8LB.

[0042] Embodiment 3:

[0043] This case provides a method for preparing glass powder and conductive copper paste, and a conductive copper paste sintering process.

[0044] (1) BaO, ZnO, B2O3 and SiO2 powders, the basic glass component raw materials, were weighed in a mass percentage of 25:50:20:5, ground and mixed into a uniform solid powder, placed in a crucible, and heated to 1100°C at a heating rate of 10°C / min and kept warm for 90 min to ensure that the glass raw materials were completely melted into glass liquid. The glass liquid was poured into a double-roll sheet mill for quenching and crushed after cooling.

[0045] (2) The mass ratio of the externally doped oxides MnO2, CaO and ZrO2 is 6:3:0.5. The externally doped glass components are ground and mixed into a uniform solid powder, which is placed in a crucible together with the base glass fragments. The temperature is raised to 900°C at a heating rate of 15°C / min and kept at this temperature for 30 min to ensure that the glass raw materials are completely melted into glass liquid. The glass liquid is poured into a double-roll sheet mill for quenching and crushed after cooling.

[0046] (3) Pour all the glass particles into a ball mill and grind them evenly using a ball mill at a speed of 200 r / min. Grind for 15 minutes and then pass through a 200-mesh sieve.

[0047] (4) Add deionized water to the coarse powder at a mass ratio of 1:2, and grind it again using a ball mill at a speed of 150 r / min. After grinding for 120 minutes, pass it through an 800-mesh sieve.

[0048] (5) Pour the ground water-glass suspension into a tray and place it in an oven for drying. After the water is completely evaporated, sieve it with a 100-mesh sieve to obtain glass powder.

[0049] (6) Glass powder, copper powder and organic carrier are mixed uniformly in a mass ratio of 10:65:25 to prepare a slurry.

[0050] (7) The slurry is coated on both ends of the ceramic body and sintered to prepare copper-terminal electrodes. The debinding temperature is 550-600°C and the temperature is kept for 30 minutes. The sintering temperature is 720°C and the temperature is kept for 12 minutes. The cooling zone is cooled from 500°C to 100°C at a cooling rate of 20°C / min.

[0051] like Figures 1 to 4 As shown in the figure, the glass powder has good high temperature wettability, with a wetting angle of 50°. After acid etching, the glass phase has no obvious cracks and a smooth morphology. After sintering, the electrode surface has good density, without holes, puncture pinholes, or bulging. The inner copper terminal electrode adheres closely to the ceramic body, and the stress is moderate and evenly distributed.

[0052] Comparative Example 1

[0053] Compared with Example 1, no MnO2 is added to the glass powder of Comparative Example 1, and its specific preparation process is the same as that of Example 1.

[0054] like Figure 1 As shown in Figures 3 and 4, the glass powder has poor high-temperature wettability, and the wetting angle is greater than 80°; after sintering, the copper terminal electrode adheres tightly to the ceramic body, the glass powder and copper powder do not match well, and the terminal tension is less than 6LB.

[0055] Comparative Example 2

[0056] Compared with Example 1, ZrO2 is not added to the glass powder of Comparative Example 2, and its specific preparation process is the same as that of Example 2.

[0057] The glass powder has good high-temperature wettability; after sintering, the copper terminal electrode adheres tightly to the ceramic body, but the glass powder has poor acid resistance, and after acid etching, obvious cracks appear in the glass phase and the morphology is irregular.

[0058] Comparative Example 3

[0059] Compared with Example 1, no CaO is added to the glass powder of Comparative Example 3, and its specific preparation process is the same as that of Example 2.

[0060] Glass powder has good high-temperature wettability; after sintering, the copper terminal electrode adheres tightly to the ceramic body, but the terminal is not dense enough.

[0061] The present invention melts the basic glass BaO-ZnO-B2O3 at high temperature into glass slag, then mixes MnO2, CaO and ZrO2 raw materials for secondary melting into glass powder, and then mixes the glass powder with copper powder and organic carrier to form a conductive copper paste, and combines the copper terminal electrode prepared by the integrated sintering process of the present invention, which has the advantages of low porosity, high sintering densification, and high electroplating pass rate. After sintering, the MLCC device has a small and moderate internal stress, strong terminal bonding, and a high pass rate for reliability tests such as solder resistance and non-destructiveness, meeting all requirements of MLCC for NP0 ceramic dielectrics for copper terminal electrode paste glass powder. The glass powder, conductive copper paste and sintering process of the present invention also have the advantages of simple preparation process, high efficiency, and high product pass rate.

Claims

1. A glass powder for NP0 ceramic MLCC, characterized in that: Ingredients include: A basic glass component and an externally doped glass component; wherein the basic glass component is BaO-ZnO-B2O3 system glass, the externally doped glass component is MnO2, CaO and ZrO2, and the mass ratio of the basic glass component to MnO2, CaO and ZrO2 is 100:3.5-6.5:1-5.5:0-1; The basic glass composition is composed of the following components in terms of oxide mass percentage: Composition: BaO 10-40%, ZnO 10-50%, B2O3 5-30%, SiO2 1-13%, total 100%.

2. A method for preparing a glass powder for NP0 ceramic MLCC as claimed in claim 1, characterized in that: The method comprises the following steps: weighing the raw materials of the basic glass components, grinding and mixing them into raw material solid powders and sintering them into glass liquid, pouring the glass liquid into a double-roll sheet rolling machine for quenching, and crushing the glass liquid into glass particles after cooling; The raw materials of the external glass component are weighed, ground and mixed into raw material solid powder and glass particles of the basic component, and fired into glass liquid; the glass liquid is poured into a double-roll sheet rolling machine for quenching, and crushed into glass particles after cooling, and the glass particles are ball-milled and sieved in sequence to obtain glass powder.

3. The method according to claim 2, characterized in that In the process of weighing the raw materials of the basic glass component, grinding and mixing them into raw material solid powder and firing them into glass liquid, the heating rate is 5-20°C / min, the firing temperature is 1000-1400°C, and the firing time is 60-150min; in the process of weighing the raw materials of the external glass component, grinding and mixing them into raw material solid powder and firing them with glass particles of the basic component into glass liquid, the heating rate is 10-20°C / min, the firing temperature is 900-1100°C, and the firing time is 20-60min; in the ball milling process, a ball mill is used for ball milling, the ball mill speed is 100-200r / min, and the ball milling time is 15-150min; in the screening process, the mesh size of the sieve is 100-800 meshes.

4. The method according to claim 3, characterized in that The ball milling includes coarse grinding and fine grinding; wherein, during the coarse grinding, the ball milling time is 10 to 90 minutes; during the fine grinding, alcohol or water needs to be added as a ball milling medium, the mass ratio of the ball milling medium to the glass powder is 2:0.5 to 4, and the ball milling time is 30 to 180 minutes; after the fine grinding process is completed, drying treatment is required before screening.

5. A conductive copper paste for NP0 ceramic MLCC, characterized in that: Ingredients include: Copper powder, an organic carrier and a glass powder for NP0 ceramic MLCC as claimed in claim 1.

6. The conductive copper paste for NP0 ceramic MLCC according to claim 5, characterized in that: The organic carrier includes resin and organic solvent, wherein the mass of the resin is 10% to 30% of the mass of the organic carrier; the mass of the organic solvent is 70% to 90% of the mass of the organic carrier; the resin is at least one of ethyl cellulose, cellulose acetate butyrate, and acrylic resin; the organic solvent is at least one of alcohol ester dodecanol, pinene alcohol, ethylene glycol butyl ether, and diethylene glycol butyl ether.

7. The conductive copper paste for NP0 ceramic MLCC according to claim 5, characterized in that: Calculated by mass percentage, the raw materials include: 50-80% copper powder, 10-30% organic carrier, and 3-18% glass powder for NP0 ceramic MLCC.

8. A process for sintering a conductive copper paste for NP0 ceramic MLCC as claimed in any one of claims 5 to 7, characterized in that: It comprises a debinding zone, a sintering zone and a cooling zone; the temperature of the debinding zone is 400-650°C, and the holding time is 10-50 minutes; the temperature of the sintering zone is 650-750°C, and the holding time is 10-30 minutes; the temperature of the cooling zone is 250-500°C, and the cooling rate is 10-30°C / min.

Citation Information

Patent Citations

  • High-sintering-compactness copper paste for MLCC and preparation method of high-sintering-compactness copper paste

    CN113724912A

  • Lead-free glass powder as well as preparation method and application thereof

    CN114409251A

  • A glass powder for low-temperature sintering MLCC end electrode paste and its preparation method

    CN114835404B

  • Glass frit and preparation method thereof, and conductive paste and preparation method thereof

    CN115836032A

  • Lead-free glass powder material as well as preparation method and application thereof

    CN115925265A

Cited By

  • High-conductivity high-temperature sintered copper paste, preparation method and application

    CN122050915A